The Impact of Animation on E-Learning Application User Engagement in Ui/Ux Design - Gloria Ganda; Betsi Rooroh; Josephin Sundah; Arnold Rondonuwu; Gabriel Spaer; Fridevy Taliwunan; Anggra Takaheghesang; Filadelfia Tulangow; David Sekeh; Kevin Saroinsong (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
The use of animated visuals to enhance the learner experience is referred to as animation in e-learning applications. Animation can be used to explain complex concepts, make learning more interactive, and improve user comprehension. A good animation can visually capture the user's attention. For example, animated page entries or element transitions can make users focus more on the content, as well as improve the aesthetics of the application, making it look more professional and attractive. In the ever-evolving app design landscape, user engagement has become an important metric for evaluating the success of an app. This research explores the impact of animation on user engagement in web user interface/user experience (UI/UX) design. Animation is well-known as a design element, but its impact on user engagement remains unexplored. Through user testing and analysis of websites with and without animation, this research seeks to provide insight into how animation affects user behavior and interaction.